THE EFFECT OF LEVERAGE, SALES GROWTH AND PROFITABILITY ON TAX AVOIDANCE - Umar, Mariyani Putri; Paramita, Ratna Wijayanti Daniar; Taufiq, Muchamad (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2021)
This study aims to determine the effect of leverage, sales growth and profitability on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. This study uses a quantitative approach method. The population in this study were 181 companies. The sampling technique used was purposive sampling method, in order to obtain 47 companies that met the criteria for 2017-2019. The results of this study can be concluded that: 1) Leverage has a negative effect on tax avoidance. The higher the company's debt, the less risk of tax avoidance. 2) Sales growth has no effect on tax avoidance because increased sales growth is an opportunity to increase high profits so that they are able to make tax payments. 3) Profitability no effect on tax avoidance due to the higher profitability, then further reduce the rate of tax avoidance a company.